2019
DOI: 10.12973/eu-jer.8.2.453
|View full text |Cite
|
Sign up to set email alerts
|

Communication and Group Work in the Multicultural Classroom: Immigrant Students’ Experiences

Abstract: The paper is part of the qualitative research project Educational Aspirations, Opportunities and Challenges for Immigrants in University Education in Iceland, conducted in Iceland's three biggest universities. The main goal of the paper is to investigate immigrant students' experiences of communication with teachers during the learning process and their perspectives on multicultural group work. Furthermore, the paper explores immigrant students' experiences of learner-centred approach and culturally responsive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…Role play and discussion format, as well as project work are much more effective and desirable for international students than teachers tend to think. These findings support the results of previous surveys [13,62,66]. Besides, our findings can support and illustrate the ideas given in [67] that low-performing students are in need of teachers' assistance not only in the academic sphere, but also in the sphere of social integration, and they might perceive group work as a means of achieving the latter.…”
Section: Discussionsupporting
confidence: 92%
“…Role play and discussion format, as well as project work are much more effective and desirable for international students than teachers tend to think. These findings support the results of previous surveys [13,62,66]. Besides, our findings can support and illustrate the ideas given in [67] that low-performing students are in need of teachers' assistance not only in the academic sphere, but also in the sphere of social integration, and they might perceive group work as a means of achieving the latter.…”
Section: Discussionsupporting
confidence: 92%
“…These interactions correspond to research suggesting that learners receive differential benefits from specific teaching techniques based upon classroom situation and background data. This is in line with some previous findings that group work can better facilitate classroom learning for second language learners (e.g., Benediktsson and Ragnarsdottir, 2019;Takeuchi et al, 2019); however the findings of worse gains for second language learners from discussions contrasts with some previous work which predicted a similar boost (Banes et al, 2018). Banes et al argued that discussions were only beneficial within a given context that encouraged equal participation.…”
Section: Discussionsupporting
confidence: 87%
“…Meanwhile, learners with an immigrant background may be more engaged in mathematics learning in group work settings (Takeuchi et al, 2019), which may result in a greater benefit for learners with a migration background. Meanwhile in a qualitative study in Iceland, Benediktsson and Ragnarsdottir (2019) found that some immigrant children had very positive experiences and others negative experiences with group work. Relatedly, another exploratory study recently indicated that high achieving children may experience group work quite differently than other children (Cera Guy et al, 2019) and that they may not be more motivated or engaged by it.…”
Section: Introductionmentioning
confidence: 99%
“…Immigrants and refugees can integrate into the school and society more easily owing to culturally responsive educators (Hill, 2020). They appreciate it when educators allow them to use their cultural backgrounds and previous experiences at the school (Benediktsson & Ragnarsdottir, 2019). In this study, it was determined that most of the teachers and a small part of the school administrators did not see refugee children as different from other children.…”
Section: Discussionmentioning
confidence: 92%